Control transfers in corporate Germany: their frequency, causes and consequences - Jens Köke (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
This study examines changes in block ownership for a large sample of listed and non-listed German firms. The frequency of block trading is similar to other countries, and the vast majority of block trades leads to changes in ultimate ownership (control transfers). Such changes are more likely for firms with high leverage, while they are less likely for larger firms and firms with high ownership concentration. Only for listed firms poor performance is related to more frequent control transfers. Control transfers are followed by increased management turnover, and for listed firms also by asset divestitures and employee layoffs.
Keywords: J63; G34; G32; 330; Corporate governance; ownership structure; management turnover; restructuring; Corporate Governance; Eigentümerstruktur; Übernahme; Reorganisation; Schätzung; Deutschland